Analysis of the Effect of Games the Sims as an Attitude Change to Millennial Generations - Kartika Sarinta; Setiawan, Albert Octavio; Astriandifa, Indira Gayatri (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2023)
Video games or online games have appeared in Indonesia since 2001. Since then, video games have grown rapidly and are in great demand. One of them is The Sims, a simulation game of daily activities in great demand by Indonesian people. The purpose of this study is to analyse changes in the behavior of the millennial generation with the emergence of the sims game. This study used a qualitative descriptive approach and conducted interviews with four informants using focus group discussion interviews as a data collection method. Using Perloff (2017), it can be concluded that this research provides a persuasive effect on players so as to create changes in behavior in terms of developing creativity and ideas that arise in the minds of players, there are changes in playing time, style of appearance, makeup, and emotional players.